Opinion '88 - A survey on Gothenburgers attitude towards mass media and society - Weibull, Lennart (University of Gothenburg, 1994)
In this survey a number of questions were put about mass media; the use of different kind of media, dailies regularly read and subscriptions, attitude toward starting a new daily paper in Göteborg, opinion on the way media follows the ethical press rules in connection with their own news covering, news service in dailies, radio and television, mixing editorial text and advertisement, occurrence of wrong and misleading information, most reliable source of information, and the meaning of opinions and statements expressed in mass media are true. Questions about radio and television dealt with changes in listening habits when the local radio started broadcasting on its own channel, opinion on the reorganization of Swedish television, access to cable-television and tele text, and how often one watches different cable-television channels. In connection with this a number of questions were put concerning the local cable-television channel Kållevisionen. Other questions dealt with the respondents confidence in how a number of institutions and groups handle their work, how different organizations and groups are treated by mass media, and what occupation one would like children or grandchildren to choose. Questions about theatre dealt with what kind of theatre one prefers, reading of theatrical reviews, visits to the theatre during the last year, main reason for going to the theatre and not going to the theatre respectively, and together with whom one visits the theatre. Above that the respondents were asked about how often a number of leisure-time activities were practised during the last year. Other questions dealt with interest in issues concerning child care, old-age care, assist for disabled persons, assist for social excluded, and assist for refugees, attitude toward the handling of these activities in Göteborg, and if there had been any changes in the way these activities were handled during the last years. Questions concerning the neighbourhood committees dealt with the information in connection with the introduction of the committees, how well informed one considered one to be, if further information was needed, and knowledge of the local activities organized by the neighbourhood committees.

I undersökningen ställs ett antal frågor om massmedia; hur ofta man brukar ta del av olika medier; vilka dagstidningar man läser regelbundet och vilka man prenumererar på; inställning till en ny tidning i Göteborg; inställning till hur olika medier följer de etiska reglerna i sin nyhetsbevakning; hur nyhetsförmedlingen fungerar i dagspress, radio och TV; sammanblandning av redaktionell text och reklam; förekomst av felaktiga och missvisande uppgifter; mest tillförlitlig nyhetskälla; samt betydelsen av att tankar och påståenden uttryckta i massmedia är sanna. Frågor om radio och TV gällde bland annat om man förändrat lyssnandet på lokalradion sedan den börjat sända i egen kanal, inställning till svensk TV:s omorganisering, tillgången till kabel-TV och text-TV och hur ofta man tittat på olika kabel-TV kanaler. I samband med detta ställdes frågor om den lokala kabel-TV kanalen Kållevisionen, vilka typer av program man brukade titta på i Kållevisionen och vilka typer av program en lokal TV-kanal bör innehålla. Andra frågor berörde förtroendet för hur olika samhällsinstitutioner och grupper sköter sitt arbete, hur massmedia behandlar olika organisationer och grupper samt vilket yrke man helst såg att barn eller barnbarn valde. Frågor om teater tog upp vilken teaterform som föredras; läsning av teaterrecensioner; teaterbesök under det senaste året; vilka teatrar som besökts; den huvudsakliga anledningen till varför man gått respektive inte gått på teater det senaste året; och med vem man brukar gå på teater. Därutöver tillfrågades man om hur ofta man utövat ett antal andra fritidsaktiviteter under det senaste året. Andra frågor berörde intresset för frågor rörande barnomsorg, äldreomsorg, handikapphjälp, hjälp åt utslagna samt hjälp åt flyktingar, inställning till hur dessa verksamheter bedrivs i Göteborg samt om någon förändring av dessa verksamheter skett under senare år. Frågor om stadsdelsnämnder (SDN) gällde informationen om införandet, hur väl insatt i frågan man ansåg sig vara, om och hur man ville ha ytterligare information samt kännedom om vilka kommunala verk-samheter SDN skall organisera.
Opinion '88 - En undersökning om Göteborgarnas inställning till massmedia och samhälle
Keywords: Media; Media; Information society; Informationssamhället; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Cultural activities and participation; Kulturaktiviteter och deltagande; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap